2017
DOI: 10.1111/his.13184
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of CD9 expression differs between tumour cells and stromal immune cells, and depends on the molecular subtype of the invasive breast carcinoma

Abstract: T-CD9 expression could be a biomarker for poor prognosis in luminal A IBC, whereas S-CD9 expression could be a marker of good prognosis in luminal B (HER2-negative) IBC. Therefore, tumour compartment-specific analyses considering molecular subtypes are necessary to study the prognostic significance of CD9 expression in IBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
1
24
1
Order By: Relevance
“…Tetraspanins contribute to numerous cellular process as cell adhesion, cell activation, or proliferation and have been implicated in several carcinogenous processes such as angiogenesis or metastasis in human cancers . Among them, CD9 was first known as a tumor suppressor but several studies showed its oncogenic and prometastatic functions, suggesting that the different partners of CD9 in TEMs could explain these different roles. In hematological malignancies, CD9 has been mainly studied in acute lymphoblastic leukemia (ALL) where it might promote cancer stem cell‐like properties and dissemination of the disease with CXCR4‐mediated migration .…”
Section: Introductionmentioning
confidence: 99%
“…Tetraspanins contribute to numerous cellular process as cell adhesion, cell activation, or proliferation and have been implicated in several carcinogenous processes such as angiogenesis or metastasis in human cancers . Among them, CD9 was first known as a tumor suppressor but several studies showed its oncogenic and prometastatic functions, suggesting that the different partners of CD9 in TEMs could explain these different roles. In hematological malignancies, CD9 has been mainly studied in acute lymphoblastic leukemia (ALL) where it might promote cancer stem cell‐like properties and dissemination of the disease with CXCR4‐mediated migration .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on human tumor cells reported associations between tetraspanin expression and tumor progression showing both reduced (CD82, CD9) and increased expression (CD151, Tspan8) in various cancer types ( 12 , 15 , 37 47 ). In patients with invasive breast cancer, it was shown that CD9 on immune cells was associated with a longer disease free survival, while CD9 expression on the tumor cells showed the opposite effect ( 48 ). The relevance of CD37 in tumor suppression has been recently shown in CD37 −/− mice that spontaneously develop B-cell lymphoma, and in patients with CD37-negative B-cell lymphoma that have poor survival ( 45 , 49 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may be important with respect to CD9 functions as Cd9 −/− transgenic adenocarcinoma mouse prostate (TRAMP) prostate cancer mice displayed increased liver metastases, but no changes to lung metastases [30]. In addition, CD9 is ubiquitously expressed and its anti-cancer functions may be dependent on its expression and interactions with other proteins in exosomes [34], other cell types such as stroma [10], and other organ sites. Therefore, a mammary specific Cd9 knockout mouse model or syngeneic engrafting of Cd9 −/− PyMT tumors into Cd9 +/+ mice may further aid in elucidating the role of CD9 in breast cancer progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Low CD9 expression in primary breast tumors is associated with higher metastatic potential, and CD9 gene expression is commonly downregulated in lymph node metastases compared to primary breast tumors [7,8].Whilst CD9 protein levels are commonly lower in breast cancers [9], which cells are expressing CD9 within tumors and which tumor sub-type is being assessed significantly affects the prognostic outcome of this. For example, patients with invasive luminal A subtype breast cancers had a poorer prognosis if they had high levels of CD9 in cancer cells, whereas patients with luminal B breast cancers had a good prognosis with CD9 protein expression in stromal cells [10]. Moreover, CD9 is overexpressed in osteotropic breast cancer cells and bone metastases compared to primary tumors and visceral metastases [11].…”
mentioning
confidence: 99%